Strategi Pengendalian Pencemaran Tukad Mati Dari Kuta Utara Hingga Kuta Selatan Berdasarkan Penentuan Status Mutu Air - Pramana Eka Putra; I Kadek Widiantara (Program Studi Teknik Lingkungan Unmas Denpasar, 2022)
Tukad Mati is a river that functions as a drainage channel and a water source for rice fields. Several embankments that have been built serve as inspection roads along the Tukad Mati cliffs. In measuring water quality parameters, it is necessary to carry out an integrated approach so that the formulation of pollution control strategies can be carried out properly. based on the Decree of the Minister of the Environment No. 115 of 2003 The status of water quality shows the level of quality condition of the source water by comparing the quality standards that have been set.The results of the study showed that the status of the water quality of the upstream and downstream parts of the dead water was lightly polluted. so that it is expected to carry out river management and empowerment by the government and the community around Tukad Mati.